(untitled) (Research, Society and Development, 2021)
The treatment of nasal fractures involves bone repositioning and its stabilization, performed through nasal packing. However, this can be extremely uncomfortable as it obliterates the nostrils and reduces or impedes nasal breathing. Devices that ensure the maintenance of airway permeability bring greater comfort to the patient in the postoperative period. Therefore, the objective of this study is to describe the use of an alternative device to preserve nasal ventilation in patients with nasal fractures, as well as to demonstrate a clinical case. The methodology used in this work was carried out in a qualitative and descriptive way, through direct collection of patient data. A 62-year-old male patient, victim of a fall from standing height, was diagnosed with a fracture of the proper bones of the nose associated with a deviated septum. He was submitted to general anesthesia, closed bone reduction and stabilization with anterior nasal packing by placing a nasogastric tube in the nostrils directed to the oropharynx region and sterile gauze directed to the nasal bones. The patient evolved well, with improved aesthetic and functional complaints. It can be concluded that the alternative device used in this clinical case promoted greater patient comfort, guaranteed the maintenance of nasal patency, in addition to its low cost and easy availability.